Determination of efficacy of a novel alginate dressing in a lethal arterial injury model in swine. Issue 10 (October 2016) - Dowling, Matthew B.; Chaturvedi, Apurva; MacIntire, Ian C.; Javvaji, Vishal; Gustin, John; Raghavan, Srinivasa R.; Scalea, Thomas M.; Narayan, Mayur
Abstract: Introduction: Alginate is a biocompatible polysaccharide that is commonly used in the pharmaceutical, biomedical, cosmetic, and food industries. Though solid dressings composed of alginate can absorb water and promote wound healing, they are not effective hemostatic materials, particularly against massive hemorrhage. The purpose of this study is to attempt to increase the hemostatic capabilities of alginate by means of hydrophobic modification. Previous studies have illustrated that modifying a different polysaccharide, chitosan, in this way enhances its hemostatic efficacy as well as its adhesion to tissue. Here, it was hypothesized that modifying alginate with hydrophobic groups would demonstrate analogous effects. Methods: Fifteen Yorkshire swine were randomized to receive hydrophobically-modified (hm) alginate lyophilized sponges (n = 5), unmodified alginate lyophilized sponges (n = 5), or standard Kerlix™ gauze dressing (n = 5) for hemostatic control. Following a splenectomy, arterial puncture (6 mm punch) of the femoral artery was made. Wounds were allowed to freely bleed for 30 s, at which time dressings were applied and compressed for 3 min in a randomized fashion. Fluid resuscitation was given to preserve the baseline mean arterial pressure. Wounds were monitored for 180 min after arterial puncture, and surviving animals were euthanized. Results: Blood loss for the hm-alginate group was significantly less than the two control groups of (1) alginate and (2) Kerlix™ gauze (p = < 0.0001). Furthermore, 80% of hm-alginate sponges were able to sustain hemostasis for the full 180 min, whereas 0% of dressings from the control groups were able to achieve initial hemostasis. Conclusions: Hm-alginate demonstrates a greatly superior efficacy, relative to unmodified alginate and Kerlix™ gauze dressings, in achieving hemostasis from a lethal femoral artery puncture in swine. This is a similar result as has been previously described when performing hydrophobic modification to chitosan. The current study further suggests that hydrophobic modification of a hydrophilic biopolymer backbone can significantly increase the hemostatic capabilities relative to the native biopolymer.